Channels of Protection: Communication, Technology, and Asylum in Cairo, Egypt - Danielson, Nora (Refuge: Canada’s Journal on Refugees, 2013)
Communication between service providers and refugees about services, legal processes, and rights helps shape refugees’ experience of asylum but has, in Cairo, Egypt, been a source of misunderstandings and conflict. Based on qualitative pilot research, this paper explores the practices, challenges, and potentials of information technologies old and new in facilitating access to asylum in this southern city. Interviews with refugee and service providers and review of previous technology-based initiatives show that although service providers tend to rely on oral information transfer, other channels—print, phone, text messaging, websites, social media—hold significant capacity for growth. Existing practices and initiatives in Cairo demonstrate the potential for technology-based projects to overcome the geographic barriers of the urban setting and the range of literacy and languages in Cairo’s refugee communities. However, service providers and refugees require further funding and institutional support if this potential is to be realized.